Comparative Diminution of Patulin Content in Apple Juice With Food-Grade Additives Sodium Bicarbonate, Vinegar, Mixture of Sodium Bicarbonate and Vinegar, Citric Acid, Baking Powder, and Ultraviolet Irradiation - Kim, Minkyeong; Shukla, Shruti; Oh, Youngsook; Chung, Soo Hyun; Kim, Myunghee (Frontiers in Pharmacology, 2018)
This study aimed to determine an optimal method for patulin (PAT) reduction for application in apple juice production. PAT levels in spiked apple juice (100 µg/L) were measured after treatment with citric acid, sodium bicarbonate, vinegar, mixture of sodium bicarbonate and vinegar, baking powder, and ultraviolet (UV) irradiation. Treatments with sodium bicarbonate and UV irradiation were most effective in reducing PAT; however, UV irradiation reduced the yellowness (b*) of apple juice. However, sodium bicarbonate treatment affected quality attributes including soluble solids, pH, and color of apple juice. The color and odor of apple juice treated with sodium bicarbonate could be recovered via addition of citric acid per the recommendations of Korean Food Additives Codex. The present results suggest that sodium bicarbonate could be considered an additive in apple juice for PAT reduction.